2021
DOI: 10.1111/flan.12541
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating technology‐based character learning in emergency remote teaching

Abstract: The Challenge Emergency remote teaching (ERT) took place amidst foreign language instructors' skepticism toward online teaching. The study reveals the impact of ERT through the lens of Chinese character instruction. What are instructors' perceptions, strategies, and needs in this area? These questions were explored through a nationwide questionnaire and follow-up interviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
2
9
1
Order By: Relevance
“…For instance, Elshami et al (2022) reported that the technological pedagogical skills of a teacher must be considered. Similar to this, the teachers' facilitation contributed to the factors affecting the students' engagement as Xu et al (2022), mentioned. Specifically, the behavioral and cognitive engagement is reported to be higher in the class that underwent teachers' facilitation compared to the class who were not (Xu et al, 2022).…”
Section: Factors Affecting Students' Engagementsupporting
confidence: 56%
See 2 more Smart Citations
“…For instance, Elshami et al (2022) reported that the technological pedagogical skills of a teacher must be considered. Similar to this, the teachers' facilitation contributed to the factors affecting the students' engagement as Xu et al (2022), mentioned. Specifically, the behavioral and cognitive engagement is reported to be higher in the class that underwent teachers' facilitation compared to the class who were not (Xu et al, 2022).…”
Section: Factors Affecting Students' Engagementsupporting
confidence: 56%
“…Similar to this, the teachers' facilitation contributed to the factors affecting the students' engagement as Xu et al (2022), mentioned. Specifically, the behavioral and cognitive engagement is reported to be higher in the class that underwent teachers' facilitation compared to the class who were not (Xu et al, 2022). Moreover, the feedback that the teacher is providing to the students was considered a positive predictor in all aspects of student engagement (Sökmen, 2021).…”
Section: Factors Affecting Students' Engagementsupporting
confidence: 56%
See 1 more Smart Citation
“…Two articles take a technology acceptance perspective to analyse language teachers' online teaching intentions. Xu, Jin, Deifell, and Angus (2021a , 2021b) surveyed Chinese language instructors working in postsecondary institutions about their perceived values and self-confidence in online teaching of Chinese characters. The participating instructors showed ambiguous attitudes towards online teaching, and their self-confidence in using online tools was affected by their prior experiences of using technology.…”
Section: The Special Collectionmentioning
confidence: 99%
“…There were a number of studies focused exclusively on college-level Mandarin Chinese as a foreign language ERLTL experiences in Western countries, including Australia, Denmark, New Zealand, the United Kingdom, and the United States. These studies analyzed Mandarin Chinese educators' beliefs in technology use (Zhang, 2020), the influence of perceived values about and self-confidence in online character teaching on adjustments to character teaching during the pandemic (Xu et al, 2021a), intention for technology-enhanced character teaching in post-pandemic times (Xu et al, 2021b), students' perceptions of online character learning (Gao, 2020), and factors influencing student participation and educators' content delivery in general during the pandemic (Wang & East, 2020;Zhao et al, 2020).…”
Section: Emerging Research On Erltlmentioning
confidence: 99%